SIFAT KUALITATIF DAN KUANTITATIF KUSKUS DI PULAU MOOR KABUPATEN NABIRE PAPUA - Supriyantono Supriyantono; M Jen Wajo AL; Killian SD; Rumetor Rumetor; Abdillah D Sawen (The East Java Biological Society, 2006)
Reserch on cuscus diversity at Moor island was carried out on November to December 2002. The aim of the research was to know qualitative and quntitative traits, feed and mating behaviour, anatomy of digestion tract and anatomy reproduction organ. Method of case study was used in the research. We found two species of cuscus at Moor island which were Phalanger orientalis and Spilocuscus maculatus. Generally, S. maculatus is bigger than P. orientalis. Both of them can be distinguished easily. Digestion tract of S. maculatus is better than P. orientalis. The form of reproduction organ of those cuscus is very specific and no differ each other.